Threat Assessment Model in Electrical Power Grid Environment - Qassim Q.S.; Jamil N.; Mahdi M.N.; Rahim F.A.; Cob Z.C.; Sidek L.M. (IOP Publishing Ltd, 2023)
Risk analysis; Risk assessment; SCADA systems; Security of data; Catastrophic consequences; Industrial controls; Management systems; National infrastructure; Penetration testing; Threat assessment models; Vulnerability assessments; Zero day vulnerabilities; Electric power transmission networks